Understanding Adolescent Financial Behavior: The Role of Lifestyle, Self-Control, and Family Socioeconomic Status in E-Money Usage - R. Suryanti Ismail; Gwen L. L. Pattinama; Philipus Wijayanto Malindir (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines adolescent e- money usage behavior in Ambon, influenced by lifestyle, self-control, and family socioeconomic status. Data from surveys, interviews, and observations were analyzed using cluster and descriptive statistical analysis. Findings show that adolescents are grouped into three behavioral categories: Good, Fair, and Poor. Higher family socioeconomic status increases spending tendencies, while low self-control leads to impulsive transactions driven by promotions and peer influence. Additionally, the more money stored in e-money, the more frequently adolescents spend without financial consideration.